Denied data access and institutional gatekeeping: Systemic barriers to scientific progress - Buthelezi, Sandile J.; Hungwe, Taurai (Edelweiss Applied Science and Technology, 2026)
Access to research data remains a cornerstone of scientific progress, yet it continues to be constrained by institutional gatekeeping and systemic inequities that undermine transparency, reproducibility, and global participation in knowledge production. The study explores how restricted data access and institutional gatekeeping create systemic obstacles to scientific advancement, considering these within broader structural, ethical, and procedural limitations. This study employed a structured literature review methodology, selecting studies according to inclusion criteria that focused on institutional, legal, ethical, and infrastructural barriers to data access. The reviewed literature was subjected to thematic and frequency-based analysis to identify recurring patterns and systemic trends, ensuring triangulated and contextually grounded findings. Results reveal that institutional practices such as power asymmetries, procedural opacity, reputational protection, and excessive ethical oversight interact with legal, commercial, infrastructural, and skill-based limitations to produce enduring barriers to data accessibility. These dynamics disproportionately affect researchers in low-resource and peripheral contexts, perpetuating cycles of exclusion and academic dependency. The paper argues that denied data access is not merely a matter of administrative inefficiency but a manifestation of deeper governance failures embedded within the political economy of research. It concludes with an integrated framework for reform, advocating transparent and standardized access protocols, independent appeal mechanisms, equitable data governance, and capacity-building strategies that balance ethical responsibility with openness. Addressing these challenges is essential for fostering a fair, collaborative, and truly global scientific enterprise.